Is Strategic Internationalization a Reality? - Marinoni, Giorgio; de Wit, Hans (International Higher Education, 2019)
This article presents a reflection on the results of the 5th IAU Global Survey to help understand to what extent the internationalization of higher education has become a strategic process at higher education institutions (HEIs) around the world. The results of the survey seem to indicate that a strategic approach to internationalization is indeed common at the majority of HEIs. Although encouraging, the results show that there is still room for improvement when it comes to financial resources and monitoring and evaluation. They also show a risk of increasing inequality between HEIs.